2015
DOI: 10.1021/jp512989q
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Activation of Acetylene by a Neutral Gold Cluster of Experimentally Known Gas-Phase Geometry

Abstract: The electronic and structural details for the acetylene selective catalytic activation by one of the few small gold clusters whose experimental gas-phase initial geometry in neutral charge state is known, the gold heptamer, are investigated. Doing an exhaustive search of the acetylene−gold heptamer ZORA scalar relativistic PW91/TZ2P configurational space, we determine the main, secondary, and also the unimportant structures relative to the catalytic activation. We found that the leading mechanism of activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 78 publications
4
19
0
Order By: Relevance
“…These effects are much better considered by the ZORA scalar relativistic method, used in the gradient‐based optimization stage. Our previous studies about the C 2 H 2 Au 7 system yielded excellent results with this combination of computational levels of theory, which were in agreement with several experimental evidences about the systems Au 7 and C 2 H 2 …”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…These effects are much better considered by the ZORA scalar relativistic method, used in the gradient‐based optimization stage. Our previous studies about the C 2 H 2 Au 7 system yielded excellent results with this combination of computational levels of theory, which were in agreement with several experimental evidences about the systems Au 7 and C 2 H 2 …”
Section: Methodssupporting
confidence: 89%
“…We have found that stochastic‐based search of suitable candidate structures for the mutual AB and Au 4 spatial disposition, and their subsequent gradient‐based optimizations, has proven to be a very successful combination of methodologies. Among stochastic‐based methods, ASCEC has demonstrated to be very effective, both for atomic and molecular clusters of diverse nature . ASCEC is a simulated annealing algorithm in which the Metropolis criterion has been modified in such a way that it is possible to ensure exhaustive scans, moving down from high energy areas to areas of the lowest possible energies for the studied adducts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the decomposition of CH 3 F/C 2 H 5 F/NH 3 /NO molecules on Al 12 Be, corresponding direct pathways have been considered. For the case of C 2 H 2 hydrogenation reaction, we have explored reaction pathways similar to the one described by Hadad and coworkers . NBO analysis has been carried out to gauge the change in atomic charges on various gas molecules on getting adsorbed on the cluster.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Therefore, it has been suggested that hydrogenation of C 2 H 2 could be an important step toward the goal of removing C 2 H 2 from the reaction cycle. To this end, Au‐based clusters can achieve this target quite successfully . In this work, we would like to explore whether Al 12 Be can act as a suitable reaction platform for all the aforementioned processes.…”
Section: Introductionmentioning
confidence: 99%